Procedimientos Para Una Eutansia Humanitaria, Eutanasia Humanitaria de Ganado Enfermo, Herido y/o Debilitado - Jan K. Shearer; Paul Nicoletti; Pedro Melendez (EDIS)
VM-156, a 16-page full-color publication by Jan K. Shearer, Paul Nicoletti and Pedro Melendez, is the Spanish language version of VM-15, "Humane Euthanasia Procedures for Sick, Injured, and/or Debilitated Livestock." It includes sections on indications for euthanasia, methods, anatomical landmarks, exsanguination, and confirmation of death. Includes references. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, April 2007.